GLYPHOSATE APPLICATION ON NATURALIZED COUNTRY WITH PENSACOLA, FOR OVERSEEDING COOL-SEASON FORAGES - Marçallo, Francisco Antonio; Pelissari, Adelino; Moraes, Anibal de (Scientia Agraria, 2006)
A field study was conducted at Fazenda Capão Redondo, in Candói – PR, Brazil, to evaluate the participation of the pensacola (Paspalum notatum) on naturalized country, with and without glyphosate application for sod suppression, for overseeding cool-season forages on a pensacola pasture. The specific objective was to evaluate the effect of glyphosate application on subsequent regrowth of the pensacola pasture. The study was conducted during 2000 and 2001 using a randomized complete block design with five treatments and two replications. A seed mixture of Lolium multiflorum, Trifolium repens, Trifolium pratense and Lotus corniculatus was oversown on the pensacola pasture after dessication with different rates of glyphosate. The treatments (T) were: T1=0; T2=0.5; T3=0.75; T4=1.0; T5=1.25 L.ha-1. The Botanal method was used to estimate the presence of the pensacola in the available dry matter on four dates (Dec-2000, Feb-2001, Jun-2001, Dec-2001). In the treatment without glyphosate, excellent pensacola suppress was observed during the cold months followed by regrowth of pensacola in the summer. Under the conditions of this trial, In the occurrence of hoar, glyphosate application was not necessary for successful establishment of the oversown species, the glyphosate application reduced the presence of pensacola in the naturalized pasture, however has regrowth of pensacola in the summer. In the occurrence of hoar the glyphosate application was not necessary for successful establishment of the oversown species.